التحكيم التجاري الدولي بين السـرية والشفافية - خيري, مرتضى عبد الله (Revue jurisprudence; Vol. 11 No 01 (2019): مجلة الاجتهاد القضائي, 2019)
Interest in international commercial arbitration, through its reliance on recourse to legal assistance in recent cases, scrutiny of issues related to judicial projects and the stimulation of relations, has attracted traders in international trade. In addition to the above, the alliances, in that it may actually be made him superior to the rest of the means. However, there is a need for transparency to support openness in arbitration. This requires answering the question. There are different opinions in this regard. Is the obligation of confidentiality in international commercial arbitration dominates all stages of the conflict from the moment it arose under international law for arbitration by the Commission Arbitration, or its scope is limited to a particular element that is covered by confidentiality, such as arbitration, to name a few.